2011
DOI: 10.4142/jvs.2011.12.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrocortisone and aminophylline on the aggregation of equine plateletsin vitro

Abstract: The purpose of this study was to evaluate in vitro the effects of hydrocortisone and aminophylline on adenosine diphosphate (ADP)-induced platelet aggregation in horses. Blood samples from 30 healthy Thoroughbred horses were collected by via jugular venipuncture to assess platelet aggregation. Platelet-rich and platelet-poor plasma were prepared from all samples by centrifugation and divided into three different aliquots. In the first aliquot, platelet aggregation was measured after platelet activation with 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
0
12
2
Order By: Relevance
“…Animal models, however, indicate impaired platelet ADP-stimulated aggregation after hydrocortisone infusion. Casella et al suggest that hydrocortisone modulates the interaction between ADP and the appropriate receptor, as well as phospholipase A2 and phospholipase C activation by thromboxane, PAF, and/or ADP [16]. These results were not confirmed by Schuerholz et al, who found no alteration of platelet receptor expression by hydrocortisone in septic patients [30].…”
Section: Prace Oryginalnecontrasting
confidence: 54%
See 4 more Smart Citations
“…Animal models, however, indicate impaired platelet ADP-stimulated aggregation after hydrocortisone infusion. Casella et al suggest that hydrocortisone modulates the interaction between ADP and the appropriate receptor, as well as phospholipase A2 and phospholipase C activation by thromboxane, PAF, and/or ADP [16]. These results were not confirmed by Schuerholz et al, who found no alteration of platelet receptor expression by hydrocortisone in septic patients [30].…”
Section: Prace Oryginalnecontrasting
confidence: 54%
“…So far, few reports have been published on the effect of corticosteroids on platelet function, most of them were veterinary medicine studies [16,18], and their results indicate a suppressive effect of exogenous glucocorticosteroids on blood platelet aggregation in animals [16,19]. These observations contrast with reports on megakaryocyte function in Cushing's disease (CD) patients.…”
Section: Introductioncontrasting
confidence: 53%
See 3 more Smart Citations